An Ecological Model for Sustainable Forest Management of Eco-system Based on Optimal Control Theory - Hasan, Md. Nazmul; Biswas, Md. Haider Ali; Uddin, Md. Sharif (Journal of Nepal Mathematical Society, 2019)
Sustainable forest management is one of the challenging issues in the present century. In this manuscript, we have employed the model of control theory to control the consequence of toxicity and illegal logging of mature trees in the ecosystem of Sundarban, the largest mangrove forest in the world. In this investigation, we have momentarily mentioned some of the fields in which these challenges are present. These fields especially consist of sustainable forest management of ecosystem. We have reflected on the modified Leslie-Gower response function to set up as the alternative resource for industries when forestry resources are devastated. The boundedness, persistence, equilibria and stability are examined along with bionomic equilibria and optimal harvesting strategy. Our main aim is to investigate the spans and applications of control theory in real life situation, especially in efficient and sustainable forest growth.